The Ukraine crisis in the Modern-Day Information Space - fakultetas, Komunikacijos (Žurnalistikos tyrimai, 2014)
Vilnius University - Kyiv Taras Shevchenko University - Warsaw University - Warsaw S. Wyszynski’s University. Scholarly Communication and Information Centre (SCIC), Vilnius University, 2014 12 04. The scientific conference “The Ukraine crisis in the modern-day information space” is a three-part event dedicated to studying the problems of European communication which emerged as a result of the conflict between Ukraine and Russia. From the point of view of communication theories, these problems of international communication concern: what are the strengths and weaknesses of information technologies in the communication of governmental institutions with the public; why members of the public are susceptible to (destructive) information; how the methods of information warfare are changing; and why information politics is part of real international politics. Being aware that the Ukraine crisis is one of Europe’s crises and presents a challenge for the whole continent, the organisers of the event—communication and political science experts—should not only seek solutions but also provide recommendations on how to develop information politics that would be beneficial to European society. The conference is hosted by the Faculty of Communication of Vilnius University (Vilnius), the Institute of International Relations of Taras Shevchenko National University (Kiev), the Institute of Journalism of the University of Warsaw, and the Institute of Media Education and Journalism of Cardinal Stefan Wyszynski University (Warsaw).